(untitled) (Journal of Universal Science Research, 2023)
The article reveals the short content of cyprinid fish and the cultivation of cyprinid fish in conditions of intensive aquaculture in Uzbekistan. In addition, as a result of the study, scientists in Uzbekistan, the average productivity of fish brought from abroad, a two-year-old Hungarian breed, grown in cages and indicative of the viability of two-year-old fish, For breeding and growing fish by intensive aquaculture methods that do not have permanent sources of water supply, but feed at the expense of spring meltwater, rain, less often from small springs and springs, as well as small lakes, including floodplain lakes.